Implementation Of Default Judgment In Article 19 Letter C Of Government Regulation Number 9 Of 1975 At The Religious Court Of Lubuk Pakam - Anshari, Muhd. Khumaidi El; Rokan, Mustapa Khamal; Yazid, Imam (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
Each husband and wife has the right to file for divorce in the Religious Court in accordance with Government Regulation Number 9 Article 19 Letter C of 1975 and Compilation of Islamic Law Number 1 Article 116 of 1991 concerning the grounds for divorce. This is stated in the judgment of the Religious Court of Lubuk Pakam Number 2612/Pdt.G/2019/PA-Lpk. The plaintiff is NL residing in Deli Serdang Regency, and the defendant is MSHN residing in Class II B Lubuk Pakam Penitentiary. It is explained in the case summary that the plaintiff and the defendant entered into marriage on February 12, 2017, and were blessed with 2 (two) children. Initially, the plaintiff's and defendant's household was harmonious and peaceful, but on April 27, 2018, the defendant was detained by the police and sentenced to 9 (nine) years in prison for the crime of "Unauthorized mediation of the sale and purchase of Class I Narcotics in non-plant form" based on the verdict of the Lubuk Pakam District Court Number 1809/Pid.Sus/2018/PN-Lbp dated October 1, 2018, and is currently incarcerated in the Class II B Lubuk Pakam Penitentiary. In the Religious Court of Lubuk Pakam, the process of implementing the default judgment was carried out in a single session during the first hearing scheduled by the Religious Court. This one-session implementation of the default judgment was only known to the Religious Court and some of the lawyers, as the community and students considered the court process to involve at least two hearings. Therefore, this research has three main issues. The results of the research and analysis of judgment Number 2612/Pdt.G/2019/PA-Lpk, and direct interviews conducted with the activist judges at the Religious Court of Lubuk Pakam, lead the author to conclude that the process of implementing the default judgment in judgment Number 2612/Pdt.G/2019/PA-Lpk at the Religious Court of Lubuk Pakam